(untitled) (Biological Sciences - PJSIR, 1997)
Compounds4-[3-oxo-l-phenyl-3-(p-chloro orp-methoxyphenyl)-propyl]-I-[4-chlorophenyl)-2-(3-methyl-5-oxo- 2-pyrazolin-l-yl) ]-thiazole (II a-b) have been prepared. The reactions of compounds (II a-b) with hydrazines in etha- nol and in acetic acid, hydroxylamine hydrochloride, aromatic aldehydes, zinc dust, Grignard reagents, P2SS and polyphosphoric acid have been investigated.